KEGIATAN PEMBINAAN KEROHANIAN KRISTEN DI LAPAS ANAK DAN WANITA KELAS II TANGERANG - Roce Marsaulina; Rajiman Andrianus Sirait (Jurnal PKM Setiadharma, 2021)
Correctional Institution is a place to carry out the construction of inmates. For those who go to prison can cause stress to their lives. The implementation of construction is one of its functions so that the target citizens can live their lives as creatures of God and good members of society. The implementation of coaching activities specifically in the spiritual field can increase one's spiritual values, even can awaken their spirit as well. The implementation method conducted in management of the jailbird using the method of lectures or preaching online through the Zoom application and also come directly to them as a form of concern and also as a solution to break the chain of pandemic Covid 19.